Evolutionary, multi-scale analysis of river bank line retreat using continuous wavelet transforms: Jamuna River, Bangladesh - Mount, Nick J.; Tate, Nicholas J.; Sarker, Maminul H.; Thorne, Colin R. (Elsevier, 2013)
In this study continuous wavelet transforms are used to explore spatio-temporal patterns of multi-scale bank line retreat along a 204 km reach of the Jamuna River, Bangladesh. A sequence of eight bank line retreat series, derived from remotely-sensed imagery for the period 1987-1999, is transformed using the Morlet mother wavelet. Bank erosion is shown to operate at several characteristic spatial and temporal scales. Local erosion and bank line retreat are shown to occur in short, well defined reaches characterised by temporal persistence at the same location, and separated by relatively stable reaches. In contrast, evidence of downstream propagation of bank line retreat patterns is evident at larger spatial scales. The intensity of localised bank line retreat (i.e. at scales of 0 - 20 km) is strongly related to the magnitude of monsoonal peak discharge, but this relationship weakens as the spatial scale of erosion increases. The potential of continuous wavelet analysis to enhancing our understanding of morphological evolution in complex fluvial systems with multi-channel planforms is discussed.